193k views
4 votes
3(2y-3)-6=-12

i am in algebra 1.

User Chank
by
5.0k points

2 Answers

2 votes

Answer:

Explanation:

here you go mate

step 1

3(2y-3)-6=-12 equation

step 2

3(2y-3)-6=-12 simplify

(3)(2y)+(3)(-3)+-6=-12

step 3

(3)(2y)+(3)(-3)+-6=-12 distribute

6y+(-9)+(-6)=-12

step 4

(6y)+(-9+-6)=-12 combine the terms

6y-15=-12

step 5

6y-15(+15)=-12(+15) add +15 to both sides

6y=3

step 6

6y/6=3/6

answer

y=1/2

User Slwr
by
5.5k points
2 votes

Answer:

y = 1/2

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define

3(2y - 3) - 6 = -12

Step 2: Solve for y

  1. Add 6 to both sides: 3(2y - 3) = -6
  2. Divide 3 on both sides: 2y - 3 = -2
  3. Add 3 to both sides: 2y = 1
  4. Divide 2 on both sides: y = 1/2
User Phinze
by
5.3k points